2017
DOI: 10.3389/fphys.2017.01012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Baseline Airway Caliber Relates to Larger Airway Sensitivity to Rostral Fluid Shift in Asthma

Abstract: Background: We have previously shown that when asthmatics go supine, fluid shifts out of the legs, accumulates in the thorax, and exacerbates lower airway narrowing. In the retrospective analysis of our previous work presented here, we test the hypothesis that the sensitivity of this process relates inversely to baseline caliber of the lower airways.Methods: Eighteen healthy (six women) and sixteen asthmatic subjects (nine women) sat for 30 min, and then lay supine for 30 min. While supine, lower body positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although, the included studies did not evaluate overnight changes in lung function, it is unlikely that exercise training will cause overnight changes if it did not change daytime lung function. Another factor that may be associated with the nocturnal worsening of asthma is the overnight rostral fluid shift from the legs to the thorax which can increase fluid accumulation in the lower airway wall, narrow airway lumen, and worsen asthma symptoms [ 25 , 26 ]. Previous studies in patients with sleep apnea have shown that physical training during the day can reduce overnight fluid shift out of the legs and improve sleep apnea severity [ 89 ] and snoring [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the included studies did not evaluate overnight changes in lung function, it is unlikely that exercise training will cause overnight changes if it did not change daytime lung function. Another factor that may be associated with the nocturnal worsening of asthma is the overnight rostral fluid shift from the legs to the thorax which can increase fluid accumulation in the lower airway wall, narrow airway lumen, and worsen asthma symptoms [ 25 , 26 ]. Previous studies in patients with sleep apnea have shown that physical training during the day can reduce overnight fluid shift out of the legs and improve sleep apnea severity [ 89 ] and snoring [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…During sleep, recumbent posture causes a reduction in the lung volumes, respiratory muscle tone, and lung compliance [ 22 24 ]. Moreover, recumbent posture also causes a shift of fluid from the legs to the thorax (rostral fluid shift) that is associated with airway narrowing in asthma [ 25 , 26 ]. In addition, during sleep there is an overnight decrease in plasma cortisol and an increase in airway inflammation, which in turn increases cholinergic tone [ 16 , 17 ], and enhances airway hyper-responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidences show that rostral fluid shift from the legs to the thorax during supine posture 19 20 and fluid overloading 21 are potential contributors to poor asthma control and nocturnal worsening of asthma symptoms. Fluid accumulation in the thorax may cause a cascade of events that exacerbate airway narrowing.…”
mentioning
confidence: 99%
“… 19 20 In order to control for the confounding effects of sleep on airway resistance, we performed a daytime study in healthy controls and patients with asthma. 19 20 We simulated nocturnal rostral fluid shift by applying lower body positive pressure with inflatable trousers. After 30 minutes, lower body positive pressure moved similar amount of fluid out of the legs to that which happens overnight.…”
mentioning
confidence: 99%
See 1 more Smart Citation